CLINICAL VALUE OF BAFF AND APRIL CONCENTRATIONS IN SYSTEMIC LUPUS ERYTHEMATOSUS - T. A. Panafidina; M. A. Sokhova; T. V. Popkova; M. V. Cherkasova; A. A. Novikov; E. N. Aleksandrova; E. L. Nasonov (Научно-практическая ревматология, 2016)
Systemic lupus erythematosus (SLE) is characterized by the pathological activation and differentiation of B lymphocytes. The B-lymphocyte stimulator (BLyS), also known as B cell-activating factor of the tumor necrosis factor family (BAFF), and its homologue, a proliferation-inducing ligand (APRIL), belong to the ligands of the tumor necrosis factor (TNF) family and play a key role in B-lymphocyte selection and survival.Objective: to determine serum BAFF and APRIL concentrations in patients with SLE and a relationship of the clinical and laboratory parameters of the disease to the level of these cytokines.Subjects and methods. The investigation enrolled 73 patients (62 women and 11 men; median age, 30.0 [28.0; 46.0] years) with SLE (disease duration, 5.0 [1.5; 11.0] years) and its high activity (the median SLEDAI-2K scores of 8 [2; 13]).Involvement of the kidneys and joints were found in 40 and 36% of cases, respectively; there were hematologic disorders in 38%, antinuclear factor (ANF) in 94.5%, and anti-double stranded DNA antibodies in 77%. The concurrent antiphospholipid syndrome was detected in 15% of the patients. 66% of the patients took glucocorticoids (GCs) (the median dose was 10 [0; 15] mg/day, calculated with reference to prednisolone), 42% received cytotoxic drugs (cyclophosphamide, mycophenolate mofetil, azathioprine); 12% used biological agents (BAs); 31.5% received no therapy at enrolment in the investigation. Serum BAFF and APRIL concentrations were estimated using an enzyme immunoassay.Results and discussion. The concentrations of BAFF and APRIL did not differ essentially in the patients with SLE and in the controls: the median level of BAFF was 0.02 [0.01; 0.64] and 0.02 [0.01; 0.03] ng/ml; that of APRIL was 2.09 [0.01; 3.80] and 0.01 [0.01; 4.16] ng/ml, respectively. The elevated concentration of BAFF (>0.82 ng/ml) was revealed in 5.5% of the patients with SLE and that of APRIL (>5.96 ng/ml) in 4.1%. There was a positive correlation between the concentration of BAFF and the level of hematuria (r = 0.261; p < 0.05) and a negative correlation with hemoglobin concentrations (r = -0.289; p < 0.05), disease duration (r = -0.261; p < 0.05), and SLICC/DI scores (r = -0.286; p < 0.05). There was a positive correlation of APRIL levels with SLEDAI-2K scores (r = 0.323; p < 0.01), ANF titer (r = 0.256; p < 0.05), and K+ concentrations (r = 0.322; p < 0.05) and a negative correlation with hemoglobin levels (r = -0.299; p < 0.05), white blood cell count (r = -0.253; p < 0.05), and glomerular filtration rate (GFR) (r = -0.299; p < 0.05). The elevated concentrations of both BAFF and APRIL were found more often in patients with lupus nephritis compared to those without this condition (p < 0.05). The patients with SLE-induced hematological disorders had a higher APRIL concentration (p < 0.05) than those without these disorders; the groups proved to be comparable in BAFF levels. As SLE activity increased (SLEDAI-2K scores of ≥8), there was a rise in the concentration of both ligands (p < 0.05).A subgroup of SLE patients (n = 26) who had received neither GCs nor other immunosuppressants or BAs was separately analyzed. In these patients, the concentration of APRIL was higher than that in the control group: 3.06 [2.09; 4.05] and 0.01 [0.01; 4.16] ng/ml (p < 0.05), there were no differences in the level of BAFF. There was a positive correlation between the level of APRIL and the concentration of creatinine (r = 0.635; p < 0.001), urea (r = 0.574; p < 0.01), and uric acid (r = 0.633; p < 0.001) and a negative correlation with the level of white blood cells (r = -0.437; p < 0.05), lymphocytes (r = -0.497; p < 0.05) and GFR (r = -0.663; p < 0.001). The BAFF concentrations correlated positively with hematuria levels (r = 0.591; p < 0.01), SLEDAI-2K scores (r = 0.413; p < 0.05), and erythrocyte sedimentation rate (r = 0.394; p < 0.05) and negatively with hemoglobin concentrations (r = -0.2488; p < 0.05) and GFR (r = -0.473; p < 0.05).Conclusion. The concentrations of BAFF and APRIL were comparable in the patients with SLE and healthy donors. The elevated levels of both BAFF and APRIL were associated with high disease active (SLEDAI-2K scores of ≥ 8) and lupus nephritis; those of APRL are related to hematological disorders. Immunosuppressive therapy (GCs, cytostatic drugs, BAs) decreased the serum concentration of APRIL in patients with SLE.